Body Fat Distribution and Associated Risk of Cardiovascular Disease in Adults With Cerebral Palsy - Shin, Hyun Iee; Jung, Se Hee (Frontiers in Neurology, 2021)
Objective: Fat distribution has increasingly been acknowledged as a more significant health parameter than general obesity, in terms of the risk of cardiovascular disease (CVD). We aimed to investigate the regional fat distribution pattern and general body fat characteristics of adults with cerebral palsy (CP), and explored the risk of CVD in this population. Methods: People aged ≥ 20 years who were diagnosed with CP were recruited between February 2014 and November 2014. The subjects underwent a structured interview, laboratory studies, and physical examination. The amount and distribution of fat were determined directly by dual-energy X-ray absorptiometry. Laboratory analysis was performed to measure total cholesterol and triglyceride, high-density lipoprotein (HDL), low-density lipoprotein, and fasting plasma glucose levels. The Framingham risk score (FRS) was used to present the 10-year risk for having CVD, and predictors such as sex, age, total cholesterol, HDL, systolic blood pressure, treatment for hypertension, and smoking status were used to calculate the FRS. Results: Ninety-nine adults (58 men, mean age 41.77 ± 8.95 years) with CP were included. The participants consisted of all five levels of the gross motor function classification system. The mean body mass index (BMI) was 22.52 ± 4.58 kg/m². According to BMI criteria, 54.9% were overweight and 27. 3% were obese. The fat mass index criteria revealed 10.1% excess fat and 7.6% obesity. In univariable regression analysis, age, the timing of physical function deterioration, and android fat percentage were associated with the FRS (p < 0.001, p < 0.001, and p = 0.007, respectively). In multiple regression analysis, the FRS was associated with age and android fat percentage, based on the following formula: “ FRS=-18.549 + 0.410* Age + 0.577 * Android percent fat (%) (R²=0.528)” (p < 0.001). Conclusions: Body fat distribution in the android area is significantly associated with future CVD risk in adults with CP.